Nicholas I of Russia. Reduced facsimile of the engraving by H. Pauquet - Internet Archive Book... (Wikimedia Commons, 1905)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons; Iconographie